(3GdeTJHg (B( (3eTJHg GdfSHI (B)s - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi de jJNP hdOG bGd TjNfG GHf GdPgHi (B: (3gPG cJGH eHGQc Le GdaGFOI ai eYQaI eG jTJHg hjJUMa ef GdCSeGA hGdCfSGH hGdcfi s
(3BNQgG (B:s
(3dhdh TjN ddHNGQi Je GdcJGH hGdMeO ddg QH GdYdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3QhGjI CHj eMeO YHO GdYRjR Hf eMeO GdHZOGOi Yf GdPgHi HBNQgG SeGYGJ efbhdI ef NWhW CUMGHgG Ydi eDda GdcJGH SfI (B741 / 743 / 747 (3hbO Je LeY GdcJGH SfI (B723s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs